The adjustment process of Sub-Saharan migrant populations in the inner city of Johannesburg - Walker, Calynn (My University, 2020)
Migration is not an easy undertaking, with stressors arising long before the physical migration has even taken place (Tabor & Milfont, 2013). The most challenging aspects of migration include saying goodbye to loved ones and a social support system, uncertainties regarding the host country and the logistics that accompany migration, such as documentation and transportation (Tabor & Milfont, 2013). This study explores aspects of the migration and adjustment processes among a group of migrants from sub-Saharan Africa living in South Africa. It also specifically examines the help-seeking behaviours that these migrant populations utilise as part of their adjustment process. This is done by exploring and describing the migration process, its challenges, and the subsequent experiences that arise throughout the migration process. This understanding of the migration process is important in conceptualising the help-seeking behaviours and support structures that are being utilised by migrant population groups. The current available literature mostly cites the reasons for help-seeking, rather than focusing on the strategies employed or the help-seeking behaviours used by migrant populations during their adjustment in a new country (Cooper, 2014). This means that current research on migration places a large focus on the physical and psychological reasons behind migrants’ decision to seek out health or mental care. Consequently, identifying and exploring the actual help-seeking behaviours employed by migrant populations during their adjustment process is overlooked. This gap in research may lead to an incomplete picture when attempting to understand the adjustment process of migrant populations. This study addresses the research gap by focusing on the different types of help-seeking behaviour as well as the support structures that migrants seek out when entering a new country–in our case, specifically, South Africa. An understanding of both these behaviours and the structures sought out may be highly beneficial for countries such as South Africa, which hosts large migrant populations, especially from other parts of Africa. Improving the general understanding of adjustment post-migration may ultimately enable host countries to improve their ability to assist those who have chosen to leave their homes behind
A research thesis submitted in partial fulfillment of the requirements for the degree of Masters in Community-Based Counselling in Psychology at the University of the Witwatersrand, 2020